Republic of Slovenia : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that Slovenia's real GDP growth accelerated to 4 1\2 percent in 2004 driven by a large positive swing in the contribution of net foreign demand, while domestic demand growth maintained momentum. Private consumption strengthened, though to a lesser extent than expected owing to an apparent increase in the propensity to save. Economic growth is expected to moderate to 4 percent in 2005, but would still be above estimates of potential. Domestic demand is expected to ease, owing to a further slowdown of inventory accumulation.